BMP-9 mediates fibroproliferation in fibrodysplasia ossificans progressiva through TGF-β signaling - Chengzhu Zhao; Yoshiko Inada; Souta Motoike; Daisuke Kamiya; Kyosuke Hino; Makoto Ikeya (EMBO Molecular Medicine)
Abstract Fibrodysplasia ossificans progressiva (FOP) is a rare genetic disorder presenting with progressive heterotopic ossification (HO) in soft tissues. Early-stage FOP is characterized by recurrent episodes of painful tissue swelling (flare-ups), with numerous proliferation-activated mesenchymal stromal cells (MSCs) subsequently causing HO. However, the mechanisms underlying flare-up progression remain unclear. In this study, we evaluated the proliferation of MSCs obtained from FOP patient-derived induced pluripotent stem cells (FOP-iPSCs) to elucidate the mechanisms underlying flare-ups and found that bone morphogenetic protein (BMP)-9 mediated enhanced proliferation by abnormal activation of transforming growth factor (TGF)-β signaling pathway in MSCs from FOP-iPSCs. In FOP model mice, elevated BMP-9 levels correlated with elevated phosphorylation of SMAD2/3 and increased cellular proliferation in the affected tissues, while systemic BMP-9 neutralization and knockout mitigated flare-ups and HO. Thus, BMP-9 aberrantly transduces TGF-β signaling and induces fibroproliferation, initiating flare-ups. This study provides novel insights into the development of future FOP therapies.